Description of Discordance Between LDL Cholesterol, Non-HDL Cholesterol, and LDL Particle Number Among Patients of a Lipid Clinic - Joshua W Gaborcik; Melissa J Snider; Margueritte Hevezi; Allison Wehr; Kavita Sharma (University of Minnesota Libraries Publishing, 2017)
Background: While LDL cholesterol measures the cholesterol content within an LDL particle (LDL-P), it may not reflect LDL-P concentrations. If discordance exists, LDL-P may better predict cardiovascular events compared to LDL-C and non-HDL cholesterol (non-HDL-C). In primary prevention patients, discordance has been associated with diabetes, ethnicity, gender, metabolic syndrome, and smoking history. Objective: To describe discordance in patients of a lipid clinic by exploring associations between patient characteristics and discordance among LDL-C, non-HDL-C, or LDL-P. Secondarily to compare proportion of patients with baseline concordance versus discordance who have ASCVD events, diagnoses of new onset diabetes or death. Methods: A retrospective, single-center cohort study at a large academic medical center was conducted. Patients establishing care from January 2009 through December 2012 with complete initial labs were included. Logistic regression models were used to explore associations between discordance and patient characteristics. Results: Of 603 patients screened, the final cohort included 166 patients with 104 (62.7%) discordant. LDL-P was the most common discordant value. Discordance was associated with gender, smoking status, use of lipid lowering medications, and achieving patient specific LDL-C goals. In terms of any event observed after initial measurements, no significant differences were detected between discordant and concordant groups. Conclusion: Within a lipid clinic population, discordance was associated with male gender, smoking status, lipid-lowering therapy, and being at patient specific LDL-C goal. While associations were found in our population, clinicians should consider measuring LDL-P to fully assess presence or extent of discordance. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties.    Type: Original Research